Biopesticides Manual Guidelines for Selecting, Sourcing, Producing and Using Biopesticides for Key Pests of Tobacco - Grunder, Julien (CABI, 2018)
This manual aims to make information resources and technical advice available in order to support the deployment of biopesticides, which include microbials (e.g. bacteria, algae, protozoa, viruses and fungi), macrobials (e.g. predatory insects, parasitoids and beneficial nematodes), botanicals, and semiochemicals. It is intended to be a one-stop shop to address the information needs of the key groups who are responsible for selecting, sourcing and using biopesticides in the tobacco production system. Chapter 2 provides information for decision makers to support selection of biopesticide active substances. It also provides guidelines for trial managers on experimental design, data collection and reporting. Chapter 3 provides guidance for sourcing biopesticides. It also includes manuals for the local production of three types of biopesticide: Trichogramma; neem [Azadirachta indica]; and fungal biopesticides such as Trichoderma. Chapter 4 presents training materials to provide an overview of biopesticides in general together with detailed information on how to work with the key biopesticides that have already been used successfully to manage key pests in tobacco.